PERANCANGAN TATA LETAK DIVISI DPM PT DIRGANTARA INDONESIA DENGAN PENDEKATAN VIRTUAL CELL MANUFACTURING SYSTEM - BINTANG OKTAVIA NIM 13414089, BETHARI
PT Dirgantara Indonesia (PTDI) is a company producing aircraft and providing maintenance services in Indonesia. In addition to partnership agreement to supply components, PTDI also produces its own products. One of them which has attracted lots of attention is N219 Nurtanio. Due to the increasing demand caused by the new product, the management plans to re-layout the production floor of DPM to increase the productivity and meet the demand targets. The current layout is still not optimal as indicated with the average lead time to successor division up to 59 days. The high lead time is caused by the low utility of the machine in which the setup time takes up to 38.9% of the total machining time. Therefore, the management needs a better layout system that can accommodate the high volume of production and product variance to increase the productivity of DPM production floor and minimize lead time. Virtual cell manufacturing system (VCMS) with the concept of single resource constrained (SRC) is implemented to combine the trade offs between process layout and cellular layout so that machines can be grouped to specific cells without any physical movements. The study is limited to the important component that contributes at least 20% to the total demand prediction ranging 2019-2020 from 6 without considering the workforce factor. The formation of virtual cells begins with the classification of part families and followed by the determination of component and machine compositions within each cell. Solutions obtained by using LINGO software. The implementation of the model results to the formation of 6 virtual cells with different composition of machines and components. The reference model is able to allocate 93 components out of 103 components observed with the total demand of 168.880 units for 2019-2020, so that there is a time savings of production with an average of 55,62 %. The results of this virtual cell design will increase system productivity and minimize the overall lead time as well.